Construção e validação de um receptor GPS para uso espacial - Albuquerque, Glauberto Leilson Alves de (2009)
Global Positioning System, or simply GPS, it is a radionavigation system developed by United States for military applications, but it becames very useful for civilian using. In the last decades Brazil has developed sounding rockets and today many projects to build micro and nanosatellites has appeared. This kind of vehicles named spacecrafts or high dynamic vehicles, can use GPS for its autonome location and trajectories controls. Despite of a huge number of GPS receivers available for civilian applications, they cannot used in high dynamic vehicles due environmental issues (vibrations, temperatures, etc.) or imposed dynamic working limits. Only a few nations have the technology to build GPS receivers for spacecrafts or high dynamic vehicles is available and they imposes rules who difficult the access to this receivers. This project intends to build a GPS receiver, to install them in a payload of a sounding rocket and data collecting to verify its correct operation when at the flight conditions. The inner software to this receiver was available in source code and it was tested in a software development platform named GPS Architect. Many organizations cooperated to support this project: AEB, UFRN, IAE, INPE e CLBI. After many phases: defining working conditions, choice and searching electronic, the making of the printed boards, assembling and assembling tests; the receiver was installed in a VS30 sounding rocket launched at Centro de Lançamento da Barreira do Inferno in Natal/RN. Despite of the fact the locations data from the receiver were collected only the first 70 seconds of flight, this data confirms the correct operation of the receiver by the comparison between its positioning data and the the trajectory data from CLBI s tracking radar named ADOUR